A reflexió mint mentálhigiénés védőfaktor a vallástanárok hivatásvégzésében - GORBAI, Gabriella Márta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
Reflection as a Protective Factor in the Vocation of Religious Education Teachers. One of the greatest challenges of teaching is that while educators nurture and support others, their own mental well-being is often neglected. This is particularly true for religious education teachers, whose vocation extends beyond professional duties to embrace spiritual and pastoral responsibilities. The complex interplay of professional expectations, authentic witness, and vocational commitment can create significant pressure. Sustaining personal resilience therefore requires special attention to protective personality traits that buffer stress and foster coping. Among these are resourcefulness, resilience, self-efficacy, self-awareness, emotional intelligence, and spiritual intelligence, all of which contribute to well-being, effectiveness, and burnout prevention. This study explores how self-reflection fosters the development of such traits and examines concrete reflective techniques that target specific capacities. Particular emphasis is placed on prayer as a form of reflective practice: in dialogue with God, the believer simultaneously engages in dialogue with the self, reviewing thoughts, desires, guilt, and gratitude. In Protestant tradition, confessional prayer and examination of conscience highlight the believer’s responsibility to reflect before God, trusting in grace. Reflection thus emerges as a conscious cognitive-emotional process that not only supports teachers’ resilience and inner resources but also offers spiritual depth. It proves to be a vital protective factor in maintaining the personal, professional, and spiritual balance of religious education teachers.